Nursery of bonylip barb fish Osteochilus hasselti in an aquaponics system - Hadiroseyani, Yani; Diatin, Iis; Faozar, Miftah Fajri; Vinasyiam, Apriana (Jurnal Akuakultur Indonesia, 2023)
Bonylip barb fish Osteochilus hasselti is traditionally cultivated as a by-product in a polyculture system due to the problem of seed availability. The increase in local market demand for O. hasselti has not been met due to the low productivity of the growers. In an effort to increase the availability of fish seeds, intensification at the nursery stage has the potential to be effective in overcoming the limitations of land and water for cultivation. The aquaponic system can maximize yields through vertical use of space and also overcome water limitations with a recirculation system. This study aimed to evaluate the effectiveness of the aquaponics system on the intensification of O. hasselti nursery. The treatment tested was the stocking density of O. hasselti at an initial length of 4.28 ± 0.52 cm and a weight of 0.73 ± 0.29 g as many as 100 ind./m2, 150 ind./m2, and 200 ind./m2 in an aquaponic system with bok choy plants (Brassica rapa subsp. chinensis). Bonylip barb fish nursery for 30 days using aquaponic system showed that the treatment resulted in maximum survival with absolute length growth, feed conversion ratio, coefficient of variation in length and weight which were not significantly different (P>0.05). At densities above 100 ind./m2, the absolute weight growth value and the specific growth rate were higher. Overall, it can be concluded that the aquaponics system can be used for O. hasselti nursery at high stocking densities with the best production performance at a stocking density of 200 ind./m2. Keywords: fish density, growth, intensification, pak choi ABSTRAK Ikan nilem Osteochilus hasselti dibudidayakan secara tradisional sebagai produk sampingan dalam sistem polikultur karena masalah ketersediaan benih. Peningkatan permintaan pasar lokal terhadap nilem belum dapat dipenuhi karena rendahnya produktivitas pembesaran. Dalam upaya meningkatkan ketersediaan benih ikan, intensifikasi pada tahap pendederan berpotensi efektif mengatasi keterbatasan lahan dan air untuk budidaya. Perkembangan teknologi budidaya dengan sistem akuaponik dapat memaksimalkan hasil melalui pemanfaatan ruang secara vertikal dan mengatasi keterbatasan air dengan sistem resirkulasi. Penelitian ini bertujuan untuk mengevaluasi efektivitas sistem akuaponik terhadap intensifikasi pendederan ikan nilem. Perlakuan yang diuji adalah padat tebar ikan nilem dengan panjang 4,28 ± 0,52 cm dan bobot 0,73 ± 0,29 g sebanyak 100 ekor/m2, 150 ekor/m2, dan 200 ekor/m2 pada sistem akuaponik dengan tanaman pak choi Brassica rapa subsp. chinensis. Pendederan nilem selama 30 hari dalam sistem akuaponik memperlihatkan bahwa perlakuan menghasilkan kelangsungan hidup serta panjang dan bobot yang tidak berbeda nyata (P>0,05). Pada kepadatan di atas 100 ekor/m2 diperoleh nilai pertumbuhan bobot mutlak dan laju pertumbuhan spesifik yang lebih tinggi. Secara keseluruhan, dapat disimpulkan bahwa sistem akuaponik dapat digunakan untuk pendederan ikan nilem pada padat tebar yang tinggi dengan kinerja produksi terbaik pada padat tebar 200 ekor/m2. Kata kunci: padat tebar, pertumbuhan, intensifikasi, pak choi